(untitled) (Bangladesh Journal of Medical Science, 2023)
Introductions: The median nerve’s occasional or persistent compression or entrapment in the carpal tunnel from the wrist to the hand causes carpal tunnel syndrome (CTS). The main symptoms are pain, tingling, swelling, and loss of grip strength and function in the thumb, index finger, middle finger, and thumb of thumb. This study examined Saudi adults’ awareness and understanding of Carpal Tunnel Syndrome and its link with demographics and chronic conditions. Material and Methods: This cross-sectional study examined adults’ knowledge, attitudes, and practices regarding carpal tunnel syndrome from 2021 to 2022 in different Saudi Arabian regions. This study used a researcher-created questionnaire. In the awareness category, general public questions included CTS clinical aspects, etiology, and effects on daily life. Practice questions covered CTS preventive and chronic diseases. Volunteers were selected following informed consent. Result: 420 participants aged 34.8 ± 13.49 years. 280 (66.6%) were male, 140 (33.3%) females. 38 (9.04%) were non-Saudi workers, while 384 were Saudis. 235 (55.9%) individuals knew about wrist CTS and 161 (38.3%) about pain. 157 (37.3%) individuals experienced thumb tingling or numbness, while 117 and 142 agreed that CTS may produce thumb weakness (27.8%) and hand grip (35.2%). The older age group reported more thumb numbness or tingling than the other groups, although there was no statistical difference (p= 0.09). CTS was not associated with chronic disease; however, diabetes was the main comorbidity in all age groups (44; 45.3%), especially in the middle age group (21; 60%). 5.4% had CTS. CTS was rare during pregnancy (0.7%), however all age groups agreed that it could influence their employment and social life (p= 0.014 and < 0.00001). The average knowledge score was 43.3 ± 40.5, whereas the awareness score was 50.1 ± 44.2. These findings indicate that Saudis were aware of CTS clinical symptoms. Conclusion: The study examined Saudi adults’ awareness and understanding of CTS and estimated the association between CTS and demographics and chronic conditions. The study found that adult CTS awareness and knowledge were sufficient and associated with age and quality of life. CTS awareness campaigns may lower risk and raise knowledge of prevention and treatment. People who work with discomfort or use computers for long periods of time without breaks are more prone to develop CTS. Larger research is needed to understand how physical exercise causes CTS. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.157-166